Tokutomi Roka, Namiko (introducción de Carlos Rubio, traducción de Rumi Sato) Gijón, España, Satori Ediciones, 2011, 306 pp. - Meza H., Virginia (Estudios de Asia y África, 2012)
Tokutomi Roka, Namiko (introducción de Carlos Rubio, traducción de Rumi Sato) Gijón, España, Satori Ediciones, 2011, 306 pp.